2023
DOI: 10.3934/jimo.2021229
|View full text |Cite
|
Sign up to set email alerts
|

Low carbon joint strategy and coordination for a dyadic supply chain with Nash bargaining fairness

Abstract: <p style='text-indent:20px;'>In the paper, fairness concern criterion is utilized to explore the coordination of a dyadic supply chain with a fairness-concerned retailer (acting as a newsvendor), who is committed to low carbon efforts. Two models are developed for stochastic demand disturbances in the forms of multiplicative case and additive case, respectively. Firstly, the optimal joint decision of the retailer and the supply chain are proposed in two scenarios, i.e., decentralized decision and the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Their findings suggested that under certain conditions, cooperative advertising and emission reduction cost-sharing contracts are more efficient than solely using cooperative advertising contracts. Chen et al [31] discussed the coordination between a dual supply chain and a retailer with a focus on fair commitment to low-carbon efforts, pointing out that coordination can be achieved through a revenue-sharing contract and a cost-sharing mechanism for low-carbon efforts.…”
Section: The Coordination Of the Lcscmentioning
confidence: 99%
“…Their findings suggested that under certain conditions, cooperative advertising and emission reduction cost-sharing contracts are more efficient than solely using cooperative advertising contracts. Chen et al [31] discussed the coordination between a dual supply chain and a retailer with a focus on fair commitment to low-carbon efforts, pointing out that coordination can be achieved through a revenue-sharing contract and a cost-sharing mechanism for low-carbon efforts.…”
Section: The Coordination Of the Lcscmentioning
confidence: 99%
“…In order to implement the "Circular Economy Promotion Law" and promote a resourcesaving and environment-friendly society, as early as 2010, the National Development and MSCRA 6,2 Reform Commission of China indicated that remanufacturing is an advanced form of "reuse" in the circular economy. However, researches on remanufacturing usually focus on product recycling channels and strategies (Pal and Sarkar, 2021;Pan and Lin, 2021), product pricing decision and coordination (Lang and Jia, 2021;Li et al, 2021a, b), emission reduction and technologies (Chen et al, 2022;Li et al, 2021a, b;Yilmaz et al, 2021), and so on, but relatively little on the sales of remanufactured products.…”
Section: Introductionmentioning
confidence: 99%
“…However, researches on remanufacturing usually focus on product recycling channels and strategies (Pal and Sarkar, 2021; Pan and Lin, 2021), product pricing decision and coordination (Lang and Jia, 2021; Li et al. , 2021a, b), emission reduction and technologies (Chen et al ., 2022; Li et al. , 2021a, b; Yilmaz et al ., 2021), and so on, but relatively little on the sales of remanufactured products.…”
Section: Introductionmentioning
confidence: 99%